High-end fashion as a social phenomenon: Exploring the perceptions of designers and consumers - Pedro, Y.; Friedmann, E.; Loureiro, S. M. C. (Journal of Retailing and Consumer Services, 2024)
Grounded on the social constructionist theory, this paper intends to compare the perceptions of the realities of high-end consumers and fashion designers on high-end brands. The main aim is to understand how the perception of luxury brands is socially constructed by designers and consumers and to explore the impact of the social interaction, specifically, the designers' realities impacting consumers' realities. The research consists of two studies. Study 1 comprised sixteen interviews with worldwide high-end fashion designers, while Study 2 considered three consumer samples (A) consumer interviews (B) consumers' tweets (n = 145,986) specifically on sixteen high-end fashion brands, and (C) consumer online questionnaire (n = 330). We found that high-end fashion designers had more negative (less positive) sentiments compared to the consumers. Designers defined different characteristics that comprise luxury brands. They tend to classify their brand category lower than the consumers. Corroborating the social constructionist theory, we found that the value of high-end brands is constructed by the designers' and consumers' interactions. Consumers gave lower value to a luxury brand if they knew that the designers were unsatisfied and critical of their work, compared to when they were satisfied and confident about it. Therefore, high-end fashion brand managers should consider the different realities of designers and consumers and their interaction in the strategic planning process to ensure designers are satisfied with their work and aligned with the brand's values and image to maintain its luxurious status and appeal to consumers.